Partisipasi Masyarakat Kampung Pekijing Dalam Mewujudkan Kampung Literasi di Kota Serang - Reisya Salsabila (Jurnal Silatene Sosial Humaniora, 2026)
This study aims to analyze the forms of community participation in the development of Pekijing. It applies Oakley’s (1991) theory of community participation, which emphasizes active contribution, organization, roles and actions, responsibility, and motivation. This research uses a qualitative method with a case study approach. The findings show that Pekijing Village in Serang City has successfully transformed its environment from a slum area into a literacy village through the active involvement of its residents. The community participated in various activities such as providing bookshelves, organizing book exchanges between houses, and forming literacy groups.